Experiencias del modelo de enseñanza-aprendizaje en un posgrado de Ortodoncia durante la pandemia COVID-19 (2022)
The virus COVID-19 pandemic is an infectious disease caused by the coronavirus that spread rapidly throughout the world. Which involved various care such as staying home, hands washing and constant use of the mask. Likewise, face-to-face classes were suspended and it was necessary to adapt to a different model of teaching and learning from home, called virtuality. This model is applied in different universities, but not all of them were prepared for the adaptation and the uncertainty generated by it. For this reason, it was decided to study the changes in the experiences of the teaching-learning model of students and professors of the Orthodontics postgraduate course in Colombia.